Effects of 16 Weeks of Cheerleading on Physical Self-Esteem and Mental Health of Female College Students - Deng, Chenliang; Yu, Qiaoyan; Luo, Ganglin; Lu, Shuiping (Frontiers in Psychology, 2022)
Objective This study aimed to analyze the influence of cheerleading on female college students’ physical self-esteem and mental health. Materials and Methods In total, 63 female college students from the University of Electronic Science and Technology of China were trained in cheerleading for 16 weeks. The scores of each sub-field of physical self-esteem and psychological symptoms were analyzed by using Physical Self-Perception Profile (PSPP) and Symptom Checklist 90 (SCL-90), respectively, at 0 and 16 weeks of the experiment. Results After 16 weeks of cheerleading exercise, female college students had significant differences in physical attractiveness (T = 4.18), physical quality (T = 4.39), and physical self-worth (T = 3.35) before and after the experiment (P < 0.01). There were significant differences in physical condition (T = 3.87) and athletic ability (T = 2.88) before and after the experiment (P < 0.05). Somatization (T = 6.485), obsessive-compulsive symptoms (T = 11.716), interpersonal sensitivity (T = 10.077), depression (T = 8.403), anxiety (T = 10.767), hostility (T = 10.866), terror (T = 9.260), paranoia (T = 10.414), psychosis (T = 9.610), sleep and eating disorders (T = 9.323), total symptom index (T = 13.245), and mean score of positive symptoms (T = 12.237) were significantly different (P < 0.01). Conclusion Cheerleading can significantly improve the level of female college students’ physical self-esteem, especially the self-esteem level of physical attractiveness, physical quality, and physical self-worth. They also experienced significant improvement in their psychological disorders, especially somatization, depression, and sleep and eating disorders, which effectively improved their overall mental health.